The Influence of the Think Pair Share Learning Model on the Learning Creativity of Class V Students at SDS Bina Taruna 1 - Rizki, Melia; Siregar, Eko Febri Syahputra (Journal of Elementary School Education, 2022)
This thesis discusses the influence of the Think Pair Share learning model on the learning creativity of fifth grade students at SDS Bina Taruna 1. The formulation of the problem in this study is how the learning creativity of class VA students before applying the Think Pair Share learning model. How is the learning creativity of VB class students before applying the conventional learning model. How is the learning creativity of VA class students after applying the Think Pair Sharelearning model. How is the learning creativity of class VB students after applying the conventional learning model. Is there a difference in students' learning creativity in classes that apply the Think Pair Share learning model with the conventional learning model. Is there an effect of the Think Pair Share learning model on the learning creativity of students in class VA SDS Bina Taruna 1. The purpose of this study was to determine the learning creativity of class VA students before applying the Think Pair Share learning model. To find out the learning creativity of class VB students before applying the conventional learning model. To find out the learning creativity of class VA students after applying the Think Pair Share learning model. To determine the learning creativity of class VB students after applying the conventional learning model. To find out the differences in students' learning creativity in classes that apply the Think Pair Share learning model with the conventional learning model. To determine the effect of the Think Pair Share learning model on the learning creativity of students in class VA SDS Bina Taruna 1. This study uses a quantitative research type that uses an experimental class and a control class. The population of this study were all fifth grade students in SDS Bina Taruna 1. While the sample of this study was using random sampling, two classes were selected as samples, namely class VA as an experimental class with 28 students and class VB as a control class with 28 participants. educate. So the total number of subjects in this study was 56 students. The research instrument used a learning creativity test, which consisted of 10 questions in the form of an essay that had been tested for validity and reliability. Based on the results of the tests carried out in the experimental class (Think Pair Share Learning Model) the average posttest results were 90 while in the control class (Conventional Learning Model) the posttest average results were 64. Learning using the Think Pair ShareLearning Model for participants VA class students showed that the ability to learn creativity was better than using the conventional learning model. The significance value is 0.000, which is 0.000 < 0.05. It is stated that there is a significant difference between the learning creativity of students in the experimental class (Think Pair Share learning model) and the control class (Conventional learning model) thus there is an influence of learning creativity on students. The value of the tcount test is 17.872, where tcount is 17.872 > ttable 1.703. So it can be concluded that the Think Pair Share learning model has a better influence on the learning creativity of students in class VA SDS Bina Taruna 1.